Flooding within functional zones in the Santa Rosa Jauregui subwatershed Queretaro, Mexico - Hernández Guerrero, Juan Alfredo; Oreano Hernández, Dulce Sonia (Revista Geográfica de América Central., 2021)
In the urban periphery of the city of Queretaro, Mexico, floods are becoming increasingly frequent and dangerous. The process seems to be accentuated as the structure and function of hydrographic watersheds are altered. The present work analyzed the occurrence of floods within functional zones in the Santa Rosa Jauregui subwatershed in the state of Queretaro, Mexico. In this regard, functional zones were elaborated with hydrogeological variables in a Geographic Information System, units and sections were defined by employing hydrogeomorphological analysis, and flood records were compiled from hemerographic research. The results indicate that the high functional zone possesses an optimal structure that benefits the watershed downstream, however, hydrogeomorphological alterations in the middle functional zone favor the occurrence of floods in the low functional zone, which finds its floodplain in an urbanized state. Through consideration of functional zones, it was determined that floods result from systemic and cumulative processes whose awareness and consideration can be used for risk management and mitigation purposes.